2007
DOI: 10.1111/j.1365-313x.2007.03114.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput mapping of cell‐wall polymers within and between plants using novel microarrays

Abstract: SummaryWe describe here a methodology that enables the occurrence of cell-wall glycans to be systematically mapped throughout plants in a semi-quantitative high-throughput fashion. The technique (comprehensive microarray polymer profiling, or CoMPP) integrates the sequential extraction of glycans from multiple organs or tissues with the generation of microarrays, which are probed with monoclonal antibodies (mAbs) or carbohydratebinding modules (CBMs) with specificities for cell-wall components. The profiles ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
353
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 297 publications
(364 citation statements)
references
References 58 publications
6
353
0
Order By: Relevance
“…1). The CoMPP profile of the non-mycorrhizal roots points to a typical cell wall pattern for angiosperms (Moller et al 2007;Fangel et al 2012), while a decrease in all of the cell wall polymers has been revealed in the ectomycorrhizal sample, except for (1 → 3)-β-d-glucan, which can be assigned to the fungus, which also contains this polymer (Balestrini et al 2012;Fig. 2).…”
Section: Hazelnut Cell Wall Composition In the Presence And Absence Omentioning
confidence: 79%
See 4 more Smart Citations
“…1). The CoMPP profile of the non-mycorrhizal roots points to a typical cell wall pattern for angiosperms (Moller et al 2007;Fangel et al 2012), while a decrease in all of the cell wall polymers has been revealed in the ectomycorrhizal sample, except for (1 → 3)-β-d-glucan, which can be assigned to the fungus, which also contains this polymer (Balestrini et al 2012;Fig. 2).…”
Section: Hazelnut Cell Wall Composition In the Presence And Absence Omentioning
confidence: 79%
“…CoMPP was carried out as described in Moller et al (2007). Cell wall polymers were extracted sequentially from 10 mg of AIR with 300 μl of 50 mM diamino-cyclo-hexane-tetra-acetic acid (CDTA), pH 7.5 and 4 M NaOH with 0.1 % v/v NaBH4 and spotted on a nitrocellulose membrane with a pore size of 0.45 μm (Whatman, Maidstone, UK) using an Arrayjet Sprint (Arrayjey, Roslin, UK).…”
Section: Comprehensive Microarray Polymer Profilingmentioning
confidence: 99%
See 3 more Smart Citations